Synthesis and characterization of Pd(II) and Ni(II) complexes of schiff bases and catalytic activity of Pd(II) complexes / Amalina Mohd Tajuddin, Hadariah Bahron and Shahrul Nizam Ahmad - Mohd Tajuddin, Amalina; Bahron, Hadariah; Ahmad, Shahrul Nizam (Research Management Institute, 2015)
Six new Pd(II) and Ni(II) metal complexes of N, O-bidentate (LI, L2) and ONNO-tetradentate (L3) Schiff base ligands have been synthesized. The compounds were characterized via various physicochemical and spectroscopic techniques namely elemental analysis (CHN), FT-IR, IHand 13C NMR as well as magnetic susceptibility measurement. All complexes showed diamagnetism indicating that they are square planar complexes. Catalytic performance ofPd(Ll)2 andPd(L2)2 were investigated for Heck cross-coupling reaction under optimum operating parameters, monitored using GC-FID for 6 h of reaction time in inert conditions. High catalytic activities of up to 90% were observed in the presence of triethylamine as base and DMA as solvent at 100°C with 1 mmol% catalyst loading. The mechanism of catalyzed Heck reaction is proposed to go through a series of conversion ofPd(0)/Pd(II).